1999
DOI: 10.1002/cjce.5450770213
|View full text |Cite
|
Sign up to set email alerts
|

The axial hydrodynamic behavior in a liquid‐solid circulating fluidized bed

Abstract: Based on experimental results from a 7.6 cm I.D. and 3 m high liquidsolid circulating fluidized bed, the liquikolid circulating fluidization regime has been separated into two zones: the initial circulating fluidization zone and the fully developed circulating fluidization zone. The distinct hydrodynamic behavior and the influence of particle properties in the two circulating fluidization zones have been studied. The overall flow structure in LSCFB, although still somewhat non-uniform, is much more uniform tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
88
3
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 6 publications
12
88
3
1
Order By: Relevance
“…In the developing flow region, located at the lower portion of the riser, solid acceleration along with a decrease in holdup was evident. At higher total velocity, solid holdup plateaus, which indicates that the solid flow enters into the fully developed zone, and was consistent to the results reported in earlier studies (Liang et al, 1997;Zheng et al, 1999;Vidyasagar et al, 2009). …”
Section: Average Solid Holdupsupporting
confidence: 91%
See 1 more Smart Citation
“…In the developing flow region, located at the lower portion of the riser, solid acceleration along with a decrease in holdup was evident. At higher total velocity, solid holdup plateaus, which indicates that the solid flow enters into the fully developed zone, and was consistent to the results reported in earlier studies (Liang et al, 1997;Zheng et al, 1999;Vidyasagar et al, 2009). …”
Section: Average Solid Holdupsupporting
confidence: 91%
“…It is noted that there exists a similar flow structure in the axial distribution of solid holdup at every section of the riser, for the given primary velocity. Vidyasagar et al, (2009), Zheng et al, (1999, Liang et al, (1997) have also reported a similar axial distribution along the riser. An increase in axial solid holdup, with increase in auxiliary velocity can also be observed, suggesting high significance of the non-mechanical valve combination, with respect to the amount of solids held up axially in the riser.…”
Section: Axial Solid Holdupmentioning
confidence: 65%
“…Ž . ported by Liang et al 1997 andZheng et al 1999 . Figure 5 shows the influence of the superficial liquid veloc-Ž .…”
Section: Resultsmentioning
confidence: 99%
“…This mechanical valve was preferred over the hydraulic valve Ž . described by Zheng et al 1999 due to the low density of the Diaion HPA25 anion-exchange particles, which made the operation of a hydraulic valve difficult.…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…Recent work has demonstrated that the flow structure of LSCFBs is quite different from either conventional liquid fluidized beds (expanded beds) or gas-solids circulating fluidized beds. In the liquidsolid circulating fluidization, particles tend to distribute uniformly in the axial direction of a riser, except for heavy particles [5], while nonuniformity appears in the radial direction with more particles at the wall [6]. Zheng and Zhu [7] characterized the microflow structure of LSCFB and also compared with that of fast fluidization in the gas-solid circulating fluidized systems.…”
Section: Introductionmentioning
confidence: 99%